Absolute Neurocritical Care Review - Levy, Zachary David (Springer International Publishing : Imprint: Springer, 2017)
This practical question and answer book covers topics within the field of neurocritical care, including aspects of neurology, neurosurgery, general critical care, and emergency medicine. Each chapter serves as a standalone test, comprised of approximately 100 questions, and closely mimics the tone and scope of the United Council for Neurologic Subspecialties (UCNS) certification exam in neurocritical care. Rationale and discussion are provided in the answers section at the end of each exam. This practical study guide will help prepare critical care fellows and residents from a variety of backgrounds (including internal medicine, neurology, anesthesiology, and emergency medicine) for the UCNS exam.
Keywords: Medicine.; Critical care medicine.; Neurology.; Neurosurgery.; elektronické knihy; electronic books